Chloral hydrate enteral infusion for sedation in ventilated children: the CHOSEN pilot study. Issue 1 (December 2017) - Joffe, Ari; Hogan, Jessica; Sheppard, Cathy; Tawfik, Gerda; Duff, Jonathan; Garcia Guerra, Gonzalo
Abstract Background We aimed to test a novel method of delivery of chloral hydrate (CH) sedation in ventilated critically ill young children. Methods Children < 12 years old, within 72 hours of admission, who were ventilated, receiving enteral tube-feeds, with intermittent CH ordered were enrolled after signed consent. Patients received a CH loading-dose of 10 mg/kg enterally, then a syringe-pump enteral infusion at 5 mg/kg/hour, increasing to a maximum of 9 mg/kg/hour. Cases were compared to historical controls matched for age group and Pediatric Risk of Mortality score (PRISM) category, using Fisher's exact test and thet test. The primary outcome was feasibility, defined as the use of an enteral CH continuous infusion without discontinuation attributable to a pre-specified potential harm. Results There were 21 patients enrolled, at age 11.4 (12.1) months, with bronchiolitis in 10 (48%), a mean Pediatric Logistic Organ Dysfunction (PELOD) score of 6.2 (5.2), and having received enteral CH continuous infusion for 4.5 (2.2) days. Infusion of CH was feasible in 20/21 (95%; 95% CI 76–99%) patients, with one (5%) adverse event of duodenal ulcer perforation on day 3 in a patient with croup receiving regular ibuprofen and dexamethasone. The CH infusion dose (mg/kg/h) on day 2 (n  = 20) was 8.9 (IQR 5.9, 9), and on day 4 (n  = 11) was 8.8 (IQR 7, 9). Days to titration of adequate sedation (defined as ≤ 3 PRN doses/shift) was 1 (IQR 0.5, 2.5), and hours to awakening for extubation was 5 (IQR 2, 9). Cases (versus controls) had less positive fluid balance at 48 h (-2 (45) vs. 26 (46) ml/kg, p  = 0.051), and a decrease in number of PRN sedation doses from 12 h pre to 12 hours post starting CH (4.7 (3.3) to 2.6 (2.8), p  = 0.009 versus 2.9 (3.9) to 3.4 (5), p  = 0.74). There were no statistically significant differences between cases and controls in inotrope scores, signs or treatment of withdrawal, or PICU days. Conclusions Delivering CH by continuous enteral infusion is feasible, effective, and may be associated with less positive fluid balance. Whether there is a risk of duodenal perforation requires further study.